Spiritual leadership : moving people on to God's agenda - Blackaby, Henry T. (Nashville, Tenn. Broadman & Holman Publishers, 2001)
Presents insights and guidance on developing and maintaining one's spiritual leadership skills.
Keywords: Leadership -- Religious aspects -- Christianity. Leader. Leadership